Coverage and Connectivity Issue in Wireless Sensor Networks - Rachit Trivedi (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2013)
Wireless sensor networks (WSNs) are an emerging area of interest in research and development. It finds use in military surveillance, health care, environmental monitoring, forest fire detection and smart environments. An important research issue in WSNs is the coverage since cost, area and lifetime are directly validated to it.In this paper we present an overview of WSNs and try to refine the coverage and connectivity issues in wireless sensor networks.